Applications of glycopolymer libraries as protein aggregation modulators and drug delivery systems - Madeira do Ó, João (2016)
The biopharmaceutical market has been on the rise for the past two decades and is expected to continue to excel, currently presenting a growing rate of more than double than conventional pharma. Traditionally this growth has been hindered by multiple formulation issues such as poor bioavailability and poor stability. Consequently, the drive to optimise the stability of protein drug candidates via formulation impels the need for development of novel excipients. Novel glycopolymer excipients were reported to confer improved protein stability in selected cases. Nonetheless,their structure-function relationship and wider applicability remain largely unknown. Here we report the synthesis of glycopolymers with different molecular architectures based on mannose, galactose, arabinose, N-acetyl glucosamine, lactose and trehalose, and nvestigate their utility as excipients for the solution formulation of a monoclonal antibody (mAb). In this thesis work the physical stability of selected antibodies was measured as the unfolding transition temperature (Tm) and aggregation onset temperature (Tagg), as a function of glycopolymer properties, such as the nature of sugar repeating unit, macromolecular architecture and concentration. Results show that, in contrast to the stabilising effect of the corresponding mono- and di-saccharide constituents, both linear and 4-arm star glycopolymers generally destabilised the antibody, decreasing both Tm and Tagg. Accelerated stability studies of a concentrated mAb solution followed the same trend, where an increasing glycopolymer:mAb molar ratio generally decreased the percentage monomer(i.e. increased soluble aggregates). Importantly, trehalose-based glycopolymers further generated visible aggregates that could not be predicted from Tm or Tagg data. The data demonstrate a complex interplay of sugar chemistry and solution concentration of synthetic glycopolymers on their modulation of protein conformational stability and aggregation propensity. The mechanisms involved in protein:glycopolymer interaction, both in solution and dry state were further investigated, thus unravelling the behaviour reported in terms of protein stabilisation. Finally, the glycopolymers were studied as drug delivery systems, acting as solubility enhancers for hydrophobic species in aqueous solutions, through the use of extrinsic fluorescent dyes.